Implementasi Perpustakaan Digital untuk Meningkatkan Minat Baca Siswa di SDN 3 Cikoneng - Firdaus, Rizqi Muhammad; Pinandita, Tito (IAI Nasional Laa Roiba Bogor, 2024)
Reading interest is an important aspect for students' intellectual and academic development at the primary school level. However, in some elementary schools, including SDN 3 Cikoneng, students' interest in reading tends to be lacking or declining. Especially in the era of rapid development of information and communication technology, utilizing information and communication technology is one of the solutions to increase students' reading interest by implementing a digital library. The purpose of this research is to design and implement a digital library at SDN 3 Cikoneng as a means to increase student interest in reading. This digital library can be accessed easily and quickly to various learning resources in digital form. The system is designed and developed with the Waterfall model with stages including Requirements Analysis, System Design, Implementation, Testing, and Maintenance. The results of this study indicate that the digital library has begun to increase student interest in reading at SD Negeri 3 Cikoneng, because it is undeniable that now students use cellphones more than their books. Through the digital library, it will be easier for students to read material books anytime and anywhere. So it is hoped that the use of digital libraries can increase student interest in reading more effectively and efficiently.